Case-Based Diagnosis and Management of Headache Disorders - Siva, Aksel; Lampl, Christian (Headache, 2015)
This book provides the practicing physician with a practical approach to the diagnosis, evaluation, and management of headache disorders based on lessons learned from real-life headache patients. Internationally well-known headache experts present cases from their own practice and discuss the evaluation and management of each case step by step. The clearly structured chapters cover initial evaluation and diagnostic work-up, imaging, differential diagnosis, interpretation of findings of further work-up, treatment options and response and key points. A wide spectrum of headache types is covered, including both primary and secondary headache disorders. The reader will learn how to diagnose and manage different headache disorders directly from the clinical experience of experts. Case-Based Diagnosis and Management of Headache Disorders will be of value for neurologists and a wide range of physicians - from those in other specialties to primary care givers.